Crimean-Congo hemorrhagic fever virus in livestock ticks and animal handler seroprevalence at an abattoir in Ghana. Issue 1 (December 2016) - Akuffo, R.; Brandful, J.; Zayed, A.; Adjei, A.; Watany, N.; Fahmy, N.; Hughes, R.; Doman, B.; Voegborlo, S.; Aziati, D.; Pratt, D.; Awuni, J.; et al.
Abstract Background Crimean-Congo Haemorrhagic Fever Virus (CCHFV) is a zoonotic virus transmitted by Ixodid ticks and causes Crimean-Congo hemorrhagic fever (CCHF) disease in humans with up to 50 % mortality rate. Methods Freshly slaughtered livestock at the Kumasi abattoir in the Ashanti Region of Ghana were examined for the presence of ticks once a month over a 6-month period from May to November 2011. The ticks were grouped into pools by species, sex, and animal source. CCHFV was detected in the ticks using reverse transcription PCR. Blood samples were collected from enrolled abattoir workers at initiation, and from those who reported fever in a preceding 30-day period during monthly visits 2–5 months after initiation. Six months after initiation, all participants who provided baseline samples were invited to provide blood samples. Serology was performed using enzyme linked immunosorbent assay (ELISA). Demographic and epidemiological data was also obtained from enrolled participants using a structured questionnaire. Results Of 428 freshly slaughtered animals comprising 130 sheep, 149 cattle, and 149 goats examined, 144 ticks belonging to the generaAmbylomma, Hyalomma andBoophilus were identified from 57 (13.3 %): 52 (34.9 %), 4 (3.1 %) and 1 (0.7 %) cattle, sheep and goat respectively. Of 97 tick pools tested, 5 pools comprising 1 pool ofHyalomma excavatum and 4 pools ofAmbylomma variegatum, collected from cattle, were positive for CCHFV. Of 188 human serum samples collected from 108 abattoir workers, 7 (3.7 %) samples from 6 persons were anti-CCHF IgG positive with one of them also being CCHF IgM positive. The seroprevalence of CCHFV identified in this study was 5.7 %. Conclusions This study detected human exposure to CCHF virus in slaughterhouse workers and also identified the CCHF virus in proven vectors (ticks) of Crimean Congo hemorrhagic fever in Ghana. The CCHFV was detected only in ticks collected from cattle, one of the livestock known to play a role in the amplification of the CCHF virus.